Abundance and life cycle of Zonocerus variegatus (Orthoptera: Pyrgomorphidae) in the humid forest zone of southern Cameroon - Messi, J.; Kekeunou, S.; Weise, Stephan F. (Wiley, 2006)
Weekly captures from January 2000 to January 2002 enabled us to study the abundance and life cycle of the variegated grasshopper, Zonocerus variegatus (Orthoptera: Pyrgomorphidae), in the humid forest zone of Southern Cameroon. We found that Z. variegatus was present throughout the year in the forest reserve and the human‐influenced zones of Yaounde and Mbalmayo in two univoltine populations, which had unequal abundance and durations. The separation of the two populations was clearer in the Yaounde and Mbalmayo developed zones than in the Mbalmayo forest reserve (undeveloped zone). The abundance of Z. variegatus varied according to the post‐embryonic stage, sex, year and season. Hatching and coupling took place during the dry and rainy seasons, whereas oviposition occurred only in the rainy season. In Cameroon, the type of life cycle of Z. variegatus observed in the humid forest zone of the south is different from that of the “Sudanian and Sahelian” zones.